The Influence of Interactive Flat Panel Media and the TGT Model on Students' Collaboration Skills - Rahmat Hendra HR; Muh. Yunus; Rego Devilla (CV Edujavare Publishing, 2026)
This study aims to analyze the effect of Interactive Flat Panel (IFP) learning media and the Team Games Tournament (TGT) cooperative learning model on students' collaboration skills at SMPN 9 Satap Maiwa, Enrekang Regency. This study uses a quantitative approach with a quasi-experimental pretest-posttest control group design. The research sample consisted of 33 eighth-grade students consisting of 17 experimental class students and 16 control class students. Data collection techniques included tests, questionnaires, observations, and documentation, with analysis using independent sample t-test, multiple linear regression, and N-Gain. The results showed that IFP media had a positive and significant effect (Sig. 0.028 < 0.05; t count 2.312 > t table 2.042) and the TGT model also had a significant effect (Sig. 0.048 < 0.05; t count 2.061 > t table 2.042). Simultaneously, both variables had a significant effect (Sig. 0.000 < 0.05; F count 74.758 > F table 3.32). The increase in students' collaboration abilities in the experimental class was higher than in the control class, which was proven through the results of the N-Gain analysis which showed a better improvement category in the experimental class, thus strengthening the effectiveness of the application of IFP media and the TGT model in learning.